Characterization of the Immune Response to Vibrio cholerae Infection in a Natural Host Model - Farr, Dustin A.; Nag, Dhrubajyoti; Withey, Jeffrey H. (Frontiers in Cellular and Infection Microbiology, 2021)
The gram-negative bacterium Vibrio cholerae causes the life-threatening diarrheal disease cholera, which is spread through the ingestion of contaminated food or water. Cholera epidemics occur largely in developing countries that lack proper infrastructure to treat sewage and provide clean water. Numerous vertebrate fish species have been found to be natural V. cholerae hosts. Based on these findings, zebrafish (Danio rerio) have been developed as a natural host model for V. cholerae. Diarrheal symptoms similar to those seen in humans are seen in zebrafish as early as 6 hours after exposure. Our understanding of basic zebrafish immunology is currently rudimentary, and no research has been done to date exploring the immune response of zebrafish to V. cholerae infection. In the present study, zebrafish were infected with either pandemic El Tor or non-pandemic, environmental V. cholerae strains and select immunological markers were assessed to determine cellular immunity and humoral immunity. Significant increases in the gene expression of two transcription factors, T-bet and GATA3, were observed in response to infection with both V. cholerae strains, as were levels of mucosal related antibodies. Additionally, the cytokine IL-13 was shown to be significantly elevated and paralleled the mucin output in zebrafish excretions, strengthening our knowledge of IL-13 induced mucin production in cholera. The data presented here further solidify the relevancy of the zebrafish model in studying V. cholerae, as well as expanding its utility in the field of cholera immunology.